Sedimentary petrology characteristics and their implications for provenance of Hoanh Bo Basin Neogene system in Quang Ninh province, north-eastern Vietnam - Tha, Hoang Van; Wysocka, Anna; Nguyẽ̂n, Quó̂c Cường; Pha, Phan Dong; Ziółkowski, Piotr (Wydawnictwa AGH, 2017)
The Hoanh Bo Basin has developed over multiple periods since the Miocene period in association with the tectonic activity of the Chi Linh-Hon Gai and Trung Luong Faults. The basin is filled with Neogene continental sediments, comprising mainly polymictic conglomerates, sandstones, siltstones, claystones, and shales. Coarser-grained polymictic deposits predominate along the northern and western margins of the basin, whereas different types of siltstones, claystones, and sandstones occur in its centre, as well as along its southern and eastern parts, toward the Ha Long Bay. The conglomerates and sandstones are composed mainly of quartz and sedimentary rock fragments, and a small amount of mica. Cement is mainly built of iron-oxide, clay or carbonate mud. The source area for the Hoanh Bo Basin sediments was located in the close vicinity of the basin. It was built of strongly weathered rocks of the Hon Gai, Ha Coi, Cat Ba Formations.
Geology, Geophysics & Environment
Keywords: conglomerate; sandstone; petrography; Hoanh Bo Basin; Neogene; Vietnam